The dynamics of emotion and activism: Grief, gender, and collective identity in revolutionary nicaragua - de Volo, Lorraine (Mobilization: An International Quarterly, 2006)
This article argues for a multidirectional and gendered understanding of the causal relationship between emotion and collective identity. Based on interviews and participant observation with core members of a Nicaraguan mothers' organization, I identify four ways in which emotion and identity are causally linked: emotion-based identity, therapy, affective bonds, and change in collective identity leading to change in grieving style. These indicate a dynamic relationship between emotion and collective identity. Furthermore, to understand emotion-based collective identity and perceptions of the emotional benefits of participation, this relationship must be understood through gendered cultural expectations about emotion.
Keywords: 1900-1999; 1990-1999; amériques; genre; militance; mouvements sociaux; nicaragua; périodes historiques; ressource en ligne; régions géographiques; thématiques; émotions; étude qualitative